Indian & Christian : the life and legacy of Pandita Ramabai - Hedlund, Roger E.; Kim, Sebastian C. H.; Johnson, Rajkumar Boaz. (Chennai : MIIS. Pune : CMS. Delhi : ISPCK., 2011)
These fifteen essays enable us to rediscover an important reformer in modern India, the Brahmin widow and Sanskrit scholar, Pandita Ramabai. Her many-stage conversion to evangelical Christianity accompanied her lifelong efforts to uplift Hindu women, beginning with high-caste widows, and to train many to become Christian evangelists. She retained her respect for her parent's Hindu tradition but sharply criticized the low esteem accorded to women in Brahmanical Scriptures. The essays focus on different facets of her remarkable life, including her lifelong efforts to uplift Hindu women, her completion of a translation of the entire Bible into Marathi, her complex conversion, and her relation to the early stages of the worldwide Pentecostal movement.
Pandita Ramabai's conversion towards Mukti : in search of companionship, integrity and faith / Sebastian Kim -- Pandita Ramabai : the first champion of empowerment of Indian women / M.D. David -- Pandita Ramabai as a global Indian stateswoman : the significance of Ramabai's leadership and influence in the International Mission project / Roger E. Hedlund -- Pandita Ramabai Saraswati in the eyes of an Indian historian / B. Narasingaraja Naidu -- Marginalisation of Ramabai in western and Indian mission history / Keith J. White -- Spelling out the fragments of a broken geography claiming Pandita Ramabai in an Indian diasporic location in the the early 20th century / D. betty Govinden -- Consuming fire : Pandita Ramabai and the early Pentecostal impulse / Edith L. Blumhofer -- Pandita Ramabai and world Christianity / Robert Eric Frykenberg -- The biblical theological contribution of Pandita Ramabai : a neglected pioneer Indian Christian feminist theologian / Rajkumar Boaz Johnson -- Ramabai's transformative and contextual hermeneutic for the kingdom of God / Paul Swarup -- Pandita Ramabai Saraswati : the convert as 'heretic' / Ivy M. Hansdak -- Pounds, dollars and rupees : Pandita Ramabai's funding of ministry -- Forging an identity fit for God and country : Pandita Ramabai as a pioneer of indigenous Christianity / Paul Joshua -- The present world-wide revival ... brought up to India' : Pandita Ramabai and the origins of Pentecostalism / Allen Anderson -- Being Indian and Christian : an introspective analysis / Plamthodathil S. Jacob.
Revised version of papers presented at an international conference held at Pune, India, during 17-20 January 2005.
Includes bibliographical references and index.
Keywords: Ramabai Sarasvati, -- 1858-1922 -- Congresses; Christian converts from Hinduism -- India -- Maharashtra -- Biography -- Congresses; Feminism -- India -- Maharashtra -- Congresses; Maharashtra (India) -- Biography -- Congresses